PENGUATAN KAPASITAS BIDANG HUKUM, GOVERNMENT RELATIONS DAN KOMUNIKASI STRATEGIS DALAM MITIGASI RISIKO REPUTASI PADA BUMN SEKTOR TRANSPORTASI - Widyaretna Buenastuti (Jurnal Pengabdian Masyarakat Berkelanjutan, 2025)
State-owned enterprises in strategic sectors face escalating legal, reputational, and policy risks in the digital transparency era. This community engagement initiative strengthened internal capacity at PT INKA (Persero) by integrating Legal, Public Relations, and Public Affairs functions through in-depth training and structured focus group discussions. Methods included media monitoring analysis, crisis mapping, PR–Litigation matrix simulation, and the implementation of an early alarm, public disruption, dan reputational crisis framework. The program improved participants’ capability in reputational risk identification, structured strategic advisory formulation, and ethical government relations protocol development. The initiative reinforced compliance culture and preventive governance mechanisms